9=4g-3

Simple and best practice solution for 9=4g-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9=4g-3 equation:


Simplifying
9 = 4g + -3

Reorder the terms:
9 = -3 + 4g

Solving
9 = -3 + 4g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-4g' to each side of the equation.
9 + -4g = -3 + 4g + -4g

Combine like terms: 4g + -4g = 0
9 + -4g = -3 + 0
9 + -4g = -3

Add '-9' to each side of the equation.
9 + -9 + -4g = -3 + -9

Combine like terms: 9 + -9 = 0
0 + -4g = -3 + -9
-4g = -3 + -9

Combine like terms: -3 + -9 = -12
-4g = -12

Divide each side by '-4'.
g = 3

Simplifying
g = 3

See similar equations:

| 12y-8y=32 | | 5x^2-269=51 | | 13+2.50h=11+3.75h | | (s+4)(s-3)=0 | | 4x+5x+9=16 | | 232=75-w | | Log(9)(x^2-6)=Log(9)(30) | | c=108x^2+108xy^2 | | -7-2x=-4 | | 4k(k+5)=0 | | 19-4j=11 | | 14=8+3k | | 5*x^3-3*x^2+8=0 | | 2r(r-4)=0 | | 12-4x-9-3x= | | 3/4x-1/2=181/4 | | 2-4x-9-3x= | | 5*x^3-3*x^2-8=0 | | 4x-5(2x-9)=6(x+5)+3 | | 10+3h=19 | | c=(6x+6y^2)18x | | 2(x-6)+4x+7=43 | | 3x-10=8x-20 | | 100=-4w-20 | | 8-5y=-27 | | 2[c+4]=3[c+5] | | 1-r=-s | | F(50)=10x+10 | | 2x(2x+1)(2x+1)=0 | | -3x+5=-2x+3 | | -7x^3-4x^2-28x-16=0 | | -7(y-6)=9y-22 |

Equations solver categories